Persuasive Strategies Used by Dr. Zakir Naik in his Speech in Oxford Union with Theme “Islam and the 21st Century” - alfian alfian; chandri febri santi; novita sari (English Language, Linguistics, Literature, And Education Journal, 2019)
This research aimed to describe about Persuasive Strategies Used by Dr. Zakir Naik in his Speech in Oxford Union with Theme Islam and the 21st Century. The background of this research is the speech that uttetrances by Dr. Zakir Naik are very give influence toward the audiences. The purpose of this study was (1) would like to find out types of persuasive strategies used by Dr. Zakir Naik in Oxford Union with theme Islam and 21st Century (2) would like to find out the ways of persuasive strategies are apply in the speech that used by Dr. Zakir Naik in Oxford Union with theme Islam and 21st century. This research used the theory of Gorys Keraf to find out types of persuasive strategies and used the theory of Aristotles to analysed the ways of apply persuasive strategies in the speech. This research used descriptive qualitative method to analyze the data. The object of this research is Dr. Zakir Naik speech in Oxford Union with theme Islam and 21st Century. The result of this research, there are types of persuasive strategies that found in Dr. Zakir Naik speech in Oxford Union with theme Islam and 21st century, there are 10 data indicated as rationalization strategy, 2 data indicated as identification, 8 data indicated as suggestion,4 data indicated as conformity, 1 indicated as compensation, 16 indicated as projection and 15 indicated as displacement. Then, also found the ways of persuasive strategies are apply in Dr. Zakir Naik speech in Oxford Union, there are 4 include as appeal to emotion, 9 include as showing evidence, 7 include as personal character of the speaker.